2020
DOI: 10.1038/s41419-020-2724-5
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy as a modulator of cell death machinery

Abstract: The balance between cell death and survival is a critical parameter in the regulation of cells and the maintenance of homeostasis in vivo. Three major mechanisms for cell death have been identified in mammalian cells: apoptosis (type I), autophagic cell death (type II), and necrosis (type III). These three mechanisms have been suggested to engage in cross talk with each other. Among them, autophagy was originally characterized as a cell survival mechanism for amino acid recycling during starvation. Whether aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
105
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(106 citation statements)
references
References 147 publications
(311 reference statements)
1
105
0
Order By: Relevance
“…2 ). At present, relevant literature has reported related factors are involved in regulating the interaction between autophagic and cell apoptosis in other tumors, such as Beclin-1, P62, caspase, Bcl-2 and so on [ 51 , 52 ]. It was also found that these related regulatory factors were involved in the interaction between autophagic and apoptosis in colorectal cancer [ 48 , 53 ] ( Fig.…”
Section: The Main Regulatory Factors Of the Interaction Between Autopmentioning
confidence: 99%
“…2 ). At present, relevant literature has reported related factors are involved in regulating the interaction between autophagic and cell apoptosis in other tumors, such as Beclin-1, P62, caspase, Bcl-2 and so on [ 51 , 52 ]. It was also found that these related regulatory factors were involved in the interaction between autophagic and apoptosis in colorectal cancer [ 48 , 53 ] ( Fig.…”
Section: The Main Regulatory Factors Of the Interaction Between Autopmentioning
confidence: 99%
“…In general, autophagy is initiated to recover ATP levels and avoid cell death when cellular energy is limited, such as during increased AMP/ATP or amino acid starvation (34). However, cellular ATP levels are also fundamental for autophagy initiation, and are required in several steps during autophagy (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is the dynamic process by which unnecessary or dysfunctional cytosolic proteins and organelles are degraded in order to maintain cell homeostasis. It is activated under extracellular (starvation, hypoxia and infection) and intracellular (accumulation of damaged molecules and high bioenergetics demand) stress conditions (200). Nutrient limitation or starvation is a frequent feature of the cellular microenvironment in the core of solid tumors.…”
Section: Circadian Clock Pancreatic Cancer and Therapymentioning
confidence: 99%
“…Nutrient limitation or starvation is a frequent feature of the cellular microenvironment in the core of solid tumors. The predominant role of autophagy in cancer cells is to confer stress tolerance, which serves to maintain tumor cell survival ( 201 ) by altering metabolic conditions ( 200 ).…”
Section: Circadian Clock Pancreatic Cancer and Therapymentioning
confidence: 99%